STUDI KEPUASAN WISATAWAN DENGAN FASILITAS DAN KUALITAS PELAYANAN DI DESA WISATA LEREP KABUPATEN SEMARANG - Yuliana Halawa; Yustina Denik Risyanti (Media Bina Ilmiah, 2022)
This study was carried out in the Lerep Tourism Village, Semarang Regency with the aim of analyzing and explaining the impact of facilities and service quality on visitor satisfaction, at a time when tourist visits are fluctuating due to several factors, such as facility infrastructure which is still considered inadequate and service quality is minimal. given to visitors. Study information was obtained from questionnaires and available data. The number of samples used in this study was 94 respondents. The information obtained is processed using descriptive analysis and quantitative statistical analysis. Application of multiple linear regression to identify the impact of independent variables on the dependent variable, as well as to test models and hypotheses. Regression analysis shows that additional facilities and service quality have an impact on tourist satisfaction. Facilities and services have a significant impact on overall visitor satisfaction. This shows that in order to increase visitor satisfaction, it is necessary to add adequate and comfortable facilities as well as the best service for tourists.